Long‐term survival of Acidovorax citrulli in citron melon (Citrullus lanatus var. citroides) seeds. (4th January 2014) - Dutta, B.; Sanders, H.; Langston, D. B.; Booth, C.; Smith, S.; Gitaitis, R. D.
<x xml:space="preserve">Abstract</x> Long‐term survival of Acidovorax citrulli in citron melon (Citrullus lanatus var. citroides) seeds was investigated. Citron melon seed lots infected with A. citrulli were generated in the field by inoculating either the pistils (stigma) or pericarps (ovary wall) of the female blossoms. Seventeen A. citrulli isolates from 14 different haplotypes belonging to two different groups (group I and II) were used for inoculation. After confirming that 100% of seed lots were infected, they were stored at 4°C and 50% RH for 7 years. After storage, the viability of A. citrulli cells from individual lots was determined by plating macerated seeds on semiselective medium as well as growing seeds for 14 days and scoring for bacterial fruit blotch symptoms. The type of A. citrulli isolate (group I or group II) used did not significantly influence bacterial survival. However, A. citrulli survival was significantly greater in seed lots generated via pistil inoculation (52·9 and 29·4%) than via pericarp inoculation (23·5 and 17·6%). Repetitive extragenic palindrome (rep)‐PCR on A. citrulli isolated from citron melon seed lots after storage displayed similar fingerprinting patterns to those of the reference strains originally used for blossom inoculation, indicating that cross‐contamination did not occur. The results indicate that A. citrulli may survive/overwinter in citron melon seeds for at least 7 years and bacterial survival in seed was influenced more by method of blossom inoculation than by the type of bacterial isolate.